Analysis of Online Marketing for Oyster Mushroom Products (Case Study in Tiga Putra Farm Southeast Sulawesi) - Jusmi Astika; Weka Gusmiarty Abdullah; Fahria Nadiryati Sadimantara (Cita konsultindo, 2023)
This study aims to (1) find out what are Tiga Putra Farm's marketing strategies in offering oyster mushroom products through online media and (2) analyze the difference in acceptance between online and offline sales. This research used a case study method on the Tiga Putra Farm oyster mushroom cultivation business in Anduonohu ​​Village, Poasia District, Kendari City, Southeast Sulawesi with the business owner being the informant in the study. The analytical method used an interactive analysis model then analyzed the online oyster mushroom marketing strategy with STP (Segmenting, Targeting, Positioning) and Marketing Mix/4P analysis, then analyzed the differences in acceptance of the Tiga Putra Farm oyster mushroom business offline and online using T-Test analysis (Independent Sample Test).